2016 IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI) 2016
DOI: 10.1109/bhi.2016.7455963
|View full text |Cite
|
Sign up to set email alerts
|

Integration of multi-modal biomedical data to predict cancer grade and patient survival

Abstract: The Big Data era in Biomedical research has resulted in large-cohort data repositories such as The Cancer Genome Atlas (TCGA). These repositories routinely contain hundreds of matched patient samples for genomic, proteomic, imaging, and clinical data modalities, enabling holistic and multi-modal integrative analysis of human disease. Using TCGA renal and ovarian cancer data, we conducted a novel investigation of multi-modal data integration by combining histopathological image and RNA-seq data. We compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…Public multi-omics datasets such as The Cancer Genome Atlas (TCGA) [5] have greatly accelerated the research for cancer study [6], including accurate cancer grading, staging, and survival prediction [7][8][9]. The cancer survival analysis can be categorized into binary classification or risk regression.…”
Section: Introductionmentioning
confidence: 99%
“…Public multi-omics datasets such as The Cancer Genome Atlas (TCGA) [5] have greatly accelerated the research for cancer study [6], including accurate cancer grading, staging, and survival prediction [7][8][9]. The cancer survival analysis can be categorized into binary classification or risk regression.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [39] used the stacking algorithm to predict membrane protein types, and the ensemble model yielded a better overall performance than its base models. Phan et al [40] developed a stacking model to predict cancer survival and reported that this model outperformed the majority-vote model. An ensemble of various machine learning models could help reduce the bias in a single machine learning algorithm to provide a much better prediction performance than single models.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is multimodal, ranging from genetic (e.g., somatic mutations) to expression (e.g., RNA-seq gene expression) to epigenetic (e.g., promoter methylation) data. Not surprisingly, there is substantial enthusiasm for causally linking the latter to the former using various modeling and secondary data analysis techniques (Jeong et al, 2015;Phan et al, 2016;Hou et al, 2018;Tian et al, 2018;Xu et al, 2018). The ultimate goals of these analyses are (i) to gain better mechanistic understanding of the underlying molecular biology of cancer, primarily by identifying important genes and their interactions; (ii) to construct compact and efficient clinical predictors (e.g., prognostic scores, indices and signatures); (iii) to associate the latter with the particular patient groups and subgroups, in the context of personalized/precision medicine.…”
Section: Introductionmentioning
confidence: 99%